Which Role Model Is More Effective in Entrepreneurship Education? An Investigation of Storytelling on Individual’s Entrepreneurial Intention - Liu, Feng; Ma, Jiangshui; Li, Ran (Frontiers in Psychology, 2019)
Entrepreneurial stories, such as the breathtaking experience of Steve Jobs, are often adopted as an effective teaching instrument to promote individuals’ entrepreneurial intentions in entrepreneurship education. Prior research highlights the role model’s influence and the positive effect of entrepreneurial stories, which is taken for granted in many circumstances. Since most research has treated storytelling in teaching as an undifferentiated whole, few researchers have teased out the distinctive effect of different types of entrepreneurial stories, namely that between successful stories and failure stories, and between idol stories and peer stories. To deepen our knowledge about how distinctive entrepreneurial stories affect entrepreneurial intentions, we conducted two experimental studies on 150 undergraduate students in entrepreneurship education programs (EEPs). Results show that, through the intermediary variable of entrepreneurial passion, both successful stories and failure stories positively influence entrepreneurial intentions as educators presumed, but successful role model stories have a greater impact than failure stories. While idol stories, rather than peer stories, are more inclined to arouse individuals’ entrepreneurial intentions. Furthermore, we find that individuals with low entrepreneurial self-efficacy are less affected by the storytelling process.